MAGNESIUM-CONTAINING DRUGS IN CARDIOVASCULAR DISEASES - A. V. Govorin; A. P. Filev (Рациональная фармакотерапия в кардиологии, 2015)
At present experimental and clinical data confirming efficacy of magnesium-containing drugs in different cardiovascular diseases are obtained. Physiological significance of magnesium is determined by its intracellular fraction. That is why it is desirable to use magnesium with the components contributing to its intracellular penetration. Magnerot deserves attention as a complex drug consisting of magnesium and orotic acid that contributes to intracellular penetration. Data of some studies on magnesium-containing drugs application in different cardiovascular diseases are presented.